PERAN MAJELIS KEHORMATAN NOTARIS DALAM MEMERIKSA KASUS PENYALAHGUNAAN JABATAN SEBAGAI NOTARIS - M. Akbar Maulana Rahman; Elvira Puspa Anggraeni; Elisabeth Adisty Novena (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Writing this article will discuss the role of the notary honorary council in examining cases of abuse of notary office. In this article, we will discuss what a notary is, what are his authorities and powers as a notary in accordance with his profession. This problem is motivated by the many cases of notary errors in carrying out their profession. For example, the number of dual land deeds that should be the role of a notary in making the deed. As a notary cohort, it is necessary to investigate several existing cases, especially those concerning notaries. In this investigation, it will be divided into several parts. Which parts will later become the authority of the notary honorary assembly. This is also related to the code of ethics as a notary. In carrying out a position, of course someone is required or required to apply in accordance with the existing code of ethics. If someone who holds a position then commits a violation or acts outside the code of ethics, it can be classified as a criminal act of violating the code of ethics. One of the codes of ethics that is highly respected in the notary profession is to behave honestly, independently and not take sides with anyone. This is then upheld in the notary profession. This study uses normative legal methods. The normative method is legal research consisting of research on legal principles, legal systematics, and legal comparisons. The sources for writing this article are from journals and articles or other reading materials as research sources. These sources are then analyzed and presented in written form to produce a scientific work that is expected to be well understood. In addition, this article is expected to be an input or source of reading for other law students